Beverage business management - JENNIFER RAGA (Canada : Society Publishing, 2020)
Discusses in detail the business management of the beverage. The book includes classifications of beverages, the role of sweeteners in the soft drink industry, and the growth in non-alcoholic beverage industry. It also explores how the beverage should work to attain maximum profits.
Keywords: BEVERAGE; MANAGEMENT; BUSINESS